The Future of Interventional Pulmonology - Arias, Sixto; Lee, Hans J. (Seminars in Respiratory and Critical Care Medicine, 2014)
Interventional pulmonology (IP) is a maturing subspecialty of pulmonary medicine focused on advanced diagnostic and therapeutic pulmonary and thoracic medical procedures for a variety of illnesses. This rapidly growing field requires highly specific knowledge and skill sets beyond its parent specialty. While the future of IP will continue to show growth, we postulate on a few upcoming technologies which may influence the field and discuss some of the challenges associated with growth in IP.
Keywords: interventional pulmonology; bronchoscopy; technology